The Effect of Intellectual Capital on Company Value of Banking Companies in Indonesia - Lay Arifah Indah Parimarma; Mahatma Kufepaksi (Pusdikra Publishing, 2023)
Intellectual capital is considered an important resource that allows companies to maintain their competitive advantage in corporate value creation efforts, but the limitations of financial statements in explaining company value and the uncertainty of the definition of intellectual capital mean that most investors' perceptions of company value still focus on the company's financial performance. Several previous studies have found different results regarding the influence between variables. This study aims to examine the effect of intellectual capital on company value with company size, leverage, and company growth as control variables. The population of this study is banking sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2010-2021. The sampling method uses purposive sampling with certain criteria and obtained samples of 29 companies. The analysis method used is multiple linear regression analysis. The results showed that Capital Employed Efficiency (CEE), Human Capital Efficiency (HCE), and Structural Capital Efficiency (SCE) were not proven to have an effect on company value. This can happen because there is no optimal involvement of intellectual capital in efforts to create added value in the banking sector, so the research is expected to increase awareness in empowering all intellectual capital it has. Future research may also expand the limitations of this study by using measurement methods and other types of industry.